Sexuality and Internet Use: The Promise and Dangers in Cyberspace - Ami Rokach (Ital Publication, 2020)
This review highlights the relationship between sexuality and Internet use, the various ways in which the Internet includes and enhances sexuality, how it affects sexual behaviors and attitudes, and the important role it has in peoples' sexual behavior, education, interaction, and satisfaction. This article also presents the 'two faces' of the Internet. It is a useful, cheap, and widely available tool which 'opens the world' to people who only need to sit by the computer, but it may also include harmful, damaging, and twisted material which could - especially for the younger generation - be harmful and misleading.